Menelisik Perilaku Belanja Masyarakat di Era Society 5.0 - Ni Made Rahayu Agustini Mertanti (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The purpose of this study is to determine people's shopping behavior in the era of society 5.0. This research is expected to provide insight into the development of science in the field of management and marketing science, besides that it is hoped that this research can be used as a reference for future researchers. Providing management expertise in achieving goals in knowing people's shopping behavior in the era of society 5.0. This research is expected to be a reference and comparison material for subsequent researchers and is eligible to obtain a Master of Management degree at the Graduate School of the National University of Education. This research is expected to be useful to provide information, knowledge and add insight for students about marketing management. The results of this study can be concluded that Fashion is the type of product that is most sought after by millennials. Fashion products offered online also have more affordable prices when compared to selling prices in offline stores. Most consumers use online marketplaces (such as Zalora, Tokopedia, Lazada and Shope) and social media (such as Tiktokshop) to shop online.